SERVQUAL on Brand Image and Relationship Equity - Kurniawan, Pebi; Sidharta, Iwan (International Review of Management and Marketing, 2016)
The purpose of this study is to determine the effect on the service quality toward brand image and the development of customer relationship. The object of research is the Umrah services in Bandung. The total respondents of this study are 187 people with proportional random sampling technique. Exploration research methods used Structural equation modeling (SEM) partial least square (PLS). The results showed that service quality was proven to give impact on equity relationship and brand image of the Umrah services. This implies that in order to improve the relationship equity Umrah services need to improve service quality and brand image so that companies can obtain optimal benefit. Keywords: service quality, brand image, relationship equity. JEL Classifications: M21, M31